Diaphragmatic flap reinforcement in delayed repair of iatrogenic oesophageal perforation - Mat Salleh, Sarif; Din, Jiffre; Mohammad Amjad, Nasser; Wan Musa, Wan Atman Said; Singh, Sharanpal; O., David (Foundation and Blackwell Publishing Asia Pty Ltd, 2010)
Iatrogenic oesophageal perforation is a life-threatening condition with a high mortality rate especially if diagnosis is delayed. The common causes include medical instrumentation such as endoscopy, and surgical procedures. We presented a case of oesophageal perforation secondary rigid endoscopy in a 40-year-old female. The patient developed left sided pneumothorax one day after the procedure. Perforation at distal oesophagus was subsequently confi rmed after a series of investigations. She underwent surgery through the left thoracoabdominal incision and the perforation was primary sutured in two layers with diaphragmatic fl ap reinforcement.